(3ZQQ GdeYGfis - (3CMeO Hf eMeO Hf Ydj, GHf adjJI , CHh GdYHGS,J (B231 (3g` s ((3Ydi Hf GdMSf Hf eMeO Hf YHO Gddg Hf GdMSjfs)
(3ChdgG (B:s
(3ShQI HQGAI eOfjI hTei GdHMhK dCfgG JHMK Yf CSQGQ GdefGabjf hJSei GdeHYKQI dbhdg EPG HYKQ eG ai GdbHhQ s
(3BNQgG (B:s
(3HGf Gddg YR hLd jbhd jcGO GdSehGJ jJaWQf efg hJTb GdCQV hJNQ GdLHGd gPG Ef OYhG ddQMef hdOkG bGd ajcJH dg ef GdGLQ Ydi bOQ Pdc s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B136s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJaSjQ hYdhe GdbQBfs